Penilaian siswa terkait aktivitas guru bimbingan dan konseling dalam meningkatkan prestasi belajar siswa - Hamam Hamam (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
Students who demand lessons at school have hope for reaching a good achievement. One indicator of the effort to encourage students to get high achievement, namely the support of the people at school, in this case the school counselor. This study aims to determine students' assessment of the activities of school counselor in improving student achievement in high school. Data were collected by using survey to 80 students as research subjects. Data analysis was done by simple descriptive technique. School counselor activities in improving student achievement in terms of role to (1) educate the use of student time, and (2) encourage students to improve learning achievement. The conclusion of this study is that students' assessment of school counselor activities in improving student achievement in SMA Bogor is still not good. It takes extra efforts from school counselor to increase their activities in encouraging students to achieve high learning achievement.